Adsorbing the magnetic superhalogen MnCl3 to realize intriguing half-metallic and spin-gapless-semiconducting behavior in zigzag or armchair SiC nanoribbon. Issue 24 (11th April 2018) - Li, Hui; Yu, Guangtao; Zhang, Zengsong; Ma, Yanfeng; Huang, Xuri; Chen, Wei
Abstract : Adsorbing a magnetic superhalogen can be an effective strategy to achieve intriguing half-metallicity and spin-gapless-semiconductor behavior in SiC nanoribbon. Abstract : By means of first-principles computations, we first propose a new and effective strategy through adsorbing the magnetic superhalogen MnCl3 to modulate the electronic and magnetic properties of zigzag- and armchair-edged SiC nanoribbons (zSiCNR and aSiCNR, respectively). In view of its large intrinsic magnetic moment and strong electron-withdrawing ability, the adsorption of magnetic superhalogen MnCl3 can introduce magnetism in the substrate SiCNR, and simultaneously induce the electron transfer process from SiCNR to MnCl3, resulting in the evident increase of electrostatic potential in the ribbon plane, like applying an electric field. As a result, the magnetic degeneracy of pristine zSiCNR can be broken and a robust ferromagnetic half-metallicity or metallicity can be observed in the modified zSiCNR systems, while a robust ferromagnetic half-metallic or spin-gapless-semiconducting behavior can be obtained in the modified aSiCNR systems. Note that both the appealing half-metallicity and spin-gapless-semiconductor behavior are key features which hold promise for future spintronic applications. Moreover, all of these new superhalogen–SiC nanosystems can possess considerably high structural stabilities. These intriguing findings will be advantageous for promoting excellent SiC-based nanomaterials in the applications of spintronics and multifunctional nanodevices in the near future.